Preliminary study on the anti-apoptotic mechanism of Astragaloside IV on radiation-induced brain cells - Liu, Xin (Int J Immunopathol Pharmacol, 2020)
With multiple targets and low cytotoxicity, natural medicines can be used as potential neuroprotective agents. The increase in oxidative stress levels and inflammatory responses in the brain caused by radiation affects cognitive function and neuronal structure, and ultimately leads to abnormal changes in neurogenesis, differentiation, and apoptosis. Astragaloside Ⅳ (AS-Ⅳ), one of the main active constituents of astragalus, is known for its antioxidant, antihypertensive, antidiabetic, anti-infarction, anti-inflammatory, anti-apoptotic and wound healing, angiogenesis, and other protective effects. In this study, the mechanism of AS-IV against radiation-induced apoptosis of brain cells in vitro and in vivo was explored by radiation modeling, which provided a theoretical basis for the development of anti-radiation Chinese herbal active molecules and brain health products. In order to study the protective mechanism of AS-IV on radiation-induced brain cell apoptosis in mice, the paper constructed a radiation-induced brain cell apoptosis model, using TUNEL staining, flow cytometry, Western blotting to analyze AS-IV resistance mechanism to radiation-induced brain cell apoptosis. The results of TUNEL staining and flow cytometry showed that the apoptosis rate of radiation group was significantly increased. The results of Western blotting indicated that the expression levels of p-JNK, p-p38, p53, Caspase-9 and Caspase-3 protein, and the ratio of Bax to Bcl-2 in radiation group were significantly increased. There was no significant difference in the expression levels of JNK and p38. After AS-IV treatment, the apoptosis was reduced and the expression of apoptosis related proteins was changed. These data suggested that AS-IV can effectively reduce radiation-induced apoptosis of brain cells, and its mechanism may be related to the phosphorylation regulation of JNK-p38.